Mineralization and carbon turnover in subarctic heath soil as affected by warming and additional litter - Rinnan, Riikka; Michelsen, Anders; Bååth, Erland; Jonasson, Sven (Soil Biology and Biochemistry, 2007)
Arctic soil carbon (C) stocks are threatened by the rapidly advancing global warming. In addition to temperature, increasing amounts of leaf litter fall following from the expansion of deciduous shrubs and trees in northern ecosystems may alter biogeochemical cycling of C and nutrients. Our aim was to assess how factorial warming and litter addition in a long-term field experiment on a subarctic heath affect resource limitation of soil microbial communities (measured by thymidine and leucine incorporation techniques), net growing-season mineralization of nitrogen (N) and phosphorus (P), and carbon turnover (measured as changes in the pools during a growing-season-long field incubation of soil cores in situ). The mainly N limited bacterial communities had shifted slightly towards limitation by C and P in response to seven growing seasons of warming. This and the significantly increased bacterial growth rate under warming may partly explain the observed higher C loss from the warmed soil. This is furthermore consistent with the less dramatic increase in the contents of dissolved organic carbon (DOC) and dissolved organic N (DON) in the warmed soil than in the soil from ambient temperature during the field incubation. The added litter did not affect the carbon content, but it was a source of nutrients to the soil, and it also tended to increase bacterial growth rate and net mineralization of P. The inorganic N pool decreased during the field incubation of soil cores, especially in the separate warming and litter addition treatments, while gross mineralized N was immobilized in the biomass of microbes and plants transplanted into the incubates soil cores, but without any significant effect of the treatments. The effects of warming plus litter addition on bacterial growth rates and of warming on C and N transformations during field incubation suggest that microbial activity is an important control on the carbon balance of arctic soils under climate change.